GluN2B and GluN2A containing NMDAR are differentially involved in extinction memory destabilization and restabilization during reconsolidation - Radiske, Andressa (2021)
Extinction memory destabilized by recall is restabilized through mTOR-dependent reconsolidation in the hippocampus, but the upstream pathways controlling these processes remain unknown. Hippocampal NMDARs drive local protein synthesis via mTOR signaling and may control active memory maintenance. We found that in adult male Wistar rats, intra dorsal-CA1 administration of the non-subunit selective NMDAR antagonist AP5 or of the GluN2A subunit-containing NMDAR antagonist TCN201 after step down inhibitory avoidance (SDIA) extinction memory recall impaired extinction memory retention and caused SDIA memory recovery. On the contrary, pre-recall administration of AP5 or of the GluN2B subunit-containing NMDAR antagonist RO25-6981 had no effect on extinction memory recall or retention per se but hindered the recovery of the avoidance response induced by post-recall intra-CA1 infusion of the mTOR inhibitor rapamycin. Our results indicate that GluN2B-containing NMDARs are necessary for extinction memory destabilization whereas GluN2A-containing NMDARs are involved in its restabilization, and suggest that pharmacological modulation of the relative activation state of these receptor subtypes around the moment of extinction memory recall may regulate the dominance of extinction memory over the original memory trace